Chinese a cappella choir Training methods and skills - Yiliang, Huang; Vadhanasiriphongs, Bhannavichaya; Samansap , Warudh; Deachmee, Kuakul (Journal of Roi Kaensarn Academi, 2024)
A Cappella has a long history and cultural tradition. It sings only by human voice without the accompaniment of any musical instrument, and shows rich and diverse musical effects through harmony, rhythm and other elements.in recent years, More inclined to integrate different musical styles (such as pop, rock, R & B, jazz, etc.), And may include more sophisticated arranger and acting skills, Also commonly used are human voices to imitate the sound of musical instruments, Such as percussion, bass, etc.Maybe even to use modern technology, Such as microphones, acoustics, etc.To enhance the audio-visual experience of the performance, It will also present good works on TV shows, social media and other platforms, Share it with more people who love music, Attracting large numbers of young audiences and performers, It is a musical cultural phenomenon that is gradually becoming popular worldwide, The same is true in senior music education, It offers fun and challenges, Suitable for cultivating the music literacy and social skills of the elderly. However, in the field of music education for the elderly, the teaching guidelines and methods of modern A Cappella have not been paid full attention and explored to suit their learning needs and psychological characteristics. This article presented Chinese a cappella choir Training methods and skills.